Circulating MicroRNA Profile as a Potential Predictive Biomarker for Early Diagnosis of Spontaneous Abortion in Patients With Subclinical Hypothyroidism - Zhou, Yingying; Wang, Xinyi; Zhang, Yuanyuan; Zhao, Tong; Shan, Zhongyan; Teng, Weiping (Frontiers in Endocrinology, 2018)
An increasing number of studies suggest that subclinical hypothyroidism (SCH) is associated with complications of gestation, including spontaneous abortion (SA). However, the underlying mechanism is not clear. MicroRNA (miRNA) has been demonstrated to be closely related to gynecological reproductive diseases. We determined miRNA expression in patients with SCH, SCH with SA (SCH+SA), and in those with SA as well as healthy controls (HC), and analyzed whether dysregulation in several miRNAs was specific to these cohorts. An Agilent Human miRNA array was used to explore miRNA levels in pooled serum samples as a pilot study, followed by a validation of selected miRNAs by real-time PCR in SCH (N=24), SA (N=19), SCH+SA (N=21), and HC cohorts (N=18). The relative expression of miR-940 was elevated in the SCH+SA group compared with SCH, SA and HC groups. In addition, miR-486-5p was up-regulated in the SCH+SA group compared with SA and HC groups, without a difference noted between SCH+SA and SCH groups. Further analysis suggested that miR-940 or miR-486-5p may be potential predictive biomarkers for the early diagnosis of SA in patients with SCH.